Nesporazumi v komunikaciji - Verdonik, Darinka (Jezik in slovstvo, 2005)
The article discusses the pragmalinguistic aspect of misunderstandigs in communication. In the first part, the author establishes a theoretical framework based on the theory of the speech acts with the aim to define various types of menaning. What follows in the central problem of the present research: to clarify the concept of misunderstanding in language use, and to define misunderstanding and different types of misunderstanding. In the final part of the article some examples of analyses are provided to illustrate come conslusions concerning the reasons for misunderstanding.
Keywords: sociolinguistics; sociolingvistika; jezikovna pragmatika; komunikacija; nesporazumi